2013
DOI: 10.1007/s13595-013-0318-4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of longitudinal and tangential maturation stresses in Eucalyptus nitens plantation trees

Abstract: & Context Tree orientation is controlled by asymmetric mechanical stresses set during wood maturation. The magnitude of maturation stress differs between longitudinal and tangential directions, and between normal and tension woods. & Aims We aimed at evaluating patterns of maturation stress on eucalypt plantation trees and their relation with growth, with a focus on tangential stress evaluation. & Methods Released maturation strains along longitudinal and tangential directions were measured around the circumfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
1
21
1
Order By: Relevance
“…However, recent analyses showed that XG in the G-fibre are not actually located inside the G-layer, but rather at the interface between G-layer and surrounding lignified layers. Finally, this model, as it pulls microfibrils against each other, should result in lateral tensile maturation stress, which is not consistent with observations that tangential maturation stress is compressive and correlated to the magnitude of longitudinal tension [21].…”
Section: Active Binding Of Microfibrilscontrasting
confidence: 78%
See 1 more Smart Citation
“…However, recent analyses showed that XG in the G-fibre are not actually located inside the G-layer, but rather at the interface between G-layer and surrounding lignified layers. Finally, this model, as it pulls microfibrils against each other, should result in lateral tensile maturation stress, which is not consistent with observations that tangential maturation stress is compressive and correlated to the magnitude of longitudinal tension [21].…”
Section: Active Binding Of Microfibrilscontrasting
confidence: 78%
“…It is usually estimated using the value of released strain and elastic properties of wood. The magnitude of released strain typically ranges between 20.3% for strong TW and þ0.2% for severe CW [7,21,75,76]. These released strains correspond to a magnitude of stress (far higher than for example turgor pressure, which typically amounts some fractions of MPa) typically ranging between þ50 MPa and 220 MPa, respectively, for TW and CW.…”
Section: Magnitude Of Maturation Stress and Released Strainsmentioning
confidence: 99%
“…so that a 0 T can serve as an indicator of r T [33]. The strain-gauge method is useful for rapidly and precisely determining the local strain.…”
Section: Growth Stress Assessmentmentioning
confidence: 99%
“…7). It yields a ''growth stress indicator'' related to the L growth strain by a factor depending on wood anisotropy, characterized by ratios of elastic constants [1,33,34].…”
Section: Growth Stress Assessmentmentioning
confidence: 99%
“…Trees control the spatial position of their axes (stem or branches) by generation of asymmetrical stress (Fournier et al 1994;Clair et al 2013). Asymmetry of maturation stresses induces a bending moment which maintains (growing branches) or corrects (accidentally tilted stem) the spatial position of axes (Alméras et al 2006).…”
Section: Introductionmentioning
confidence: 99%